THE INVESTIGATION OF STUDENTS’ PERCEPTION AND PROBLEMS TOWARD USING BLENDED LEARNING METHOD IN ENGLISH CLASS - Farikha, Ninik; Hamida, Ulfi Dina (Jurnal Pendidikan Bahasa Inggris Proficiency, 2023)
Blended learning is one of popular methods used in this period to improve student’s skill in EFL course. There are various problems that have been found in implementing blended learning to the students in the class from positive to negative impact. This study investigates student’s perception and problems in the implementation of blended learning in their EFL courses. Collected data will be analyzed in qualitative descriptive method. This research was only conducted with one English class in electric engineering students of Islamic University of Kediri. The result shows most of students have positive views on both online and offline learning that used blended learning as the method. On the other hand some students still have problem while joining online learning. One of their main reasons is technical problem such as internet connection, e-learning programme and etc.